Recensement du diabète héréditaire au niveau de l’hôpital centrale de Mostaganem. - Guellil, Halima (My University, 2021)
The term diabetes designates a set of serious and long-lasting conditions, responsible for considerable morbidity and mortality in our country. Diabetes, in addition to specific risks, is a source of disabling and costly complications. Moreover, diabetes involves daily treatment for the patient, until the end of his life. So there are currently no curative treatments. The implementation of treatments go through a medical organization of care, but also and above all through an important and permanent vigilance of the patient who must acquire real competence in the face of the disease. As such, diabetes is sometimes viewed as the model for chronic disease. However, there are many ways to prevent it or control its development. To achieve effective diabetes control, it is important to educate the public and professional circles about risk factors and symptoms. The objective of our work is to collect information, which will focus mainly on the quality of the care of diabetics in the city of Mostaganem. .This work is also an opportunity to recall the forms of prevention whose advantages are not neglect, such as health education
Keywords: Chronic diseases, Diabetes, Treatment,Type1,Type2